Pola Konsumsi Makanan Kariogenik dengan Kejadian Karies Gigi pada Anak Sekolah Dasar: Ariogenic Food Consumption Pattern with the Incidence of Dental Caries in Elementary School Children - Hamzah, Acep (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Dental caries are a disease that damages tissue caused by emial and dentine Demineralization especially school-age children generally caries due to high interest and become a favorite in consuming kariogenic food So that the consumption pattern of karyogenic foods is very high. The purpose of this research is to know the relationship of consumption patterns of karyogenic foods with dental caries. Method: Design research using descriptive analytic and cross-sectional approach in 131 elementary school children with the technique of random sampling. Questionnaire to measure consumption patterns of karyogenic foods ie FFQ (food frequency questionnaire) and dental caries test with DMF- T (Decay Missing Filled-Teeth). The analysis of this research uses the Chi-square test. Result: This study describes the high carcinogenic food consumption pattern of 77 respondents (58.8%), and children with dental caries of 33 respondents (61.1%). Describing the food consumption pattern of kariogenic foods with the incidence of dental caries on the children of SDN Rangkapan Jaya Baru Depok with results and P- value (0.000). Discussion: The pattern of consumption of cariogenic food with the incidence of dental caries in children at SDN X showed the majority of the pattern of consumption of high cariogenic food and children with dental caries. The results of the analysis show that there is a relationship between cariogenic food consumption patterns and the incidence of dental caries in children. In conclusion there was a relationship of kariogenic food consumption pattern with the incidence of dental caries.